Contract — alternative form of nurse’s employment in hospital - Labuda, Daria; Chorążewicz, Marta (Nursing Problems / Problemy Pielęgniarstwa, 2013)
Employers increasingly willing to take a nursing staff to work at hospitals on the basis of a civil-law contract. Everyone who satisfies the conditions of law can conduct business activity. For example nurses may conduct individual nursing practice (applies to nurses with current license to practice). Nurses which decide to work civil-law contact must consider all of advantages and disadvantages of this form of employment. The purpose of this study was to compare two forms of employment nurses at hospitals-employment contract and civil-law agreement. In the work used method of literature review about nursing employment at hospitals based on civil-law contract. In the present study articles of the Labour Code, Civil Code and The Nurse and Midwife Professions Act were also analyzed. Contractual agreement was analyzed based on contract for health services in hospital X. Nurses employed on the basis of labor contract and civil-law agreement perform the same range of health activities. Correctly formulated civil-law agreement must be corresponding with the Civil Code. Can’t say which models of nursing employment at hospitals is the most favourable.